The Effect of strategic vigilance on competitive performance of telecommunications companies within S.A.R - عسلية فراس; صقور مجد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research examined the four dimensions of strategic vigilance, which are: competitive vigilance, commercial vigilance, technological vigilance, environmental vigilance, and their impact on the level of competitive performance in the cellular communications companies under study. The research was based on the deductive approach in describing the research variables. It also relied on the statistical survey method, and used the questionnaire tool, which was distributed to a sample of 390 employees within the general administrations of cellular communications companies operating in the Syrian Arab Republic (Syriatel, MTN) from all administrative levels. The data was analyzed using the SPSS statistical analysis program. The most important search results of are: There is a significant effect of strategic vigilance on competitive performance, The most influential axes in competitive performance is the variable technological vigilance, followed by competitive vigilance, then commercial vigilance, and finally environmental vigilance.